TWO TRICHOTROPID GASTROPODS COLLECTED BY THE ICEBREAKER SHIRASE FROM BREID BAY, ANTARCTICA, WITH PROPOSAL OF A NEW SUBGENUS (Eleventh Symposium on Polar Biology) - ヌマナミ, ヒデキ; オクタニ, タカシ; NUMANAMI, Hideki; OKUTANI, Takashi (National Institute of Polar Research, 1990)
P(論文) Among the benthos materials collected by the icebreaker "SHIRASE" from Breid Bay, Antarctica, two species of Antarctic trichotropid gastropods, Neoconcka insignis SMITH and Torellia (Schismospira subgen. n.) planispira (SMITH), were discovered. The morphological details of these two species are described and some considerations to their generic position are given. departmental bulletin paper